2014
DOI: 10.1002/jaba.151
|View full text |Cite
|
Sign up to set email alerts
|

Generalization of negatively reinforced mands in children with autism

Abstract: Each day, people encounter stimuli they find unpleasant. Some children with autism may require systematic instruction to acquire the communication skills necessary to request the termination of such aversive stimuli. We taught 2 school-aged boys with autism a mand (e.g., signing "stop") that could be used to escape a variety of aversive stimuli. First, we employed a systematic assessment to identify aversive stimuli to use during training. We then conducted mand training sequentially across those stimuli until… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 41 publications
5
25
0
Order By: Relevance
“…This finding is consistent with previous studies demonstrating that negatively-reinforced mands can generalize to untrained stimuli (Groskreutz et al, 2014;Yi et al, 2006). Moreover, it provides supporting evidence that for the two children with ASD included in this study, the newly acquired mands generalized as a result of mand training without additional programming.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This finding is consistent with previous studies demonstrating that negatively-reinforced mands can generalize to untrained stimuli (Groskreutz et al, 2014;Yi et al, 2006). Moreover, it provides supporting evidence that for the two children with ASD included in this study, the newly acquired mands generalized as a result of mand training without additional programming.…”
Section: Discussionsupporting
confidence: 92%
“…One aspect pertains to the manding function targeted during training. Although the manding function of escaping or avoiding nonpreferred or aversive stimuli is one of the first communicative functions to emerge in children (Carpenter, Mastergeorge, & Coggins, 1983), a limited number of investigators have addressed the topic of teaching negatively-reinforced mands to escape to children with ASD (Dyer & Kohland, 1991;Frost & Bondy, 2002;Groskreutz et al, 2014;Yi et al, 2006). The participants in the studies above were children with autism between the at LAURENTIAN UNIV LIBRARY on June 5, 2016 bmo.sagepub.com Downloaded from ages of 4 and 9 years.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This functional approach is consistent with the goal of radical behaviorism, which is the prediction and control of behavior (Skinner, 1953). The aforementioned conceptualization by Groskreutz et al (2014) of task aversiveness as an MO (specifically an EO) illustrates the functional nature of the concept's definition because the experimental preparation was able to demonstrate, at a minimum, the value-altering effect of task aversiveness on escape as a negative reinforcer. Interestingly, task aversiveness can also be described as a setting event because it meets the concept's lesser requirement of a demonstrated relation to behavior.…”
Section: On the Distinction Between The Motivating Operation And Settmentioning
confidence: 68%
“…1 A contemporary example of the use of the MO concept is illustrated by Groskreutz et al (2014) who taught children how to request that an aversive activity be terminated (i.e., negatively reinforced mands). The authors demonstrated that such responses were rarely emitted in the absence of aversive stimuli or in the presence of preferred stimuli, even when activity escape was available as a consequence.…”
Section: On the Distinction Between The Motivating Operation And Settmentioning
confidence: 99%